Oncogene-directed small molecule inhibitors for the treatment of cutaneous melanoma. (May 2015) - Eliades, Philip; Flaherty, Keith T; Tsao, Hensin
SUMMARY : Achievements in cancer genetics and molecular biology have revolutionized the treatment options available for advanced melanoma. Patients with certain molecularly defined melanomas have been the most fortunate beneficiaries of recently US FDA-approved therapies that target aberrant MAPK pathway signaling, yet response rates and duration of response remain suboptimal. Furthermore, many patients harbor melanomas for which no approved targeted therapies currently exist. Since the approval of vemurafenib, a selective BRAF V600E inhibitor, in 2011, there has been a surge of preclinical and clinical studies aimed at developing novel targeted therapies for a wide range of molecularly defined melanomas. In this review, we will examine the present status and future potential of molecularly targeted therapies directed at the most significant oncogenic signaling pathways in melanoma.